Times of transition: Judea in the early Hellenistic period - Honigman, Sylvie; Nihan, Christophe; Lipshits, ʿOded (Mosaics, 2021)
The chronological frame, politics and identity -- The history of rural settlement in Judea -- The workings of empires in local and comparative perspectives -- The Pentateuch : early Greek translations and receptions -- Biblical texts in the 3rd century BCE.